Assessment of Hybrid Geoids in Chile and Spain, Combining Ggm and Observations for Gnss/Leveling - Caverlotti-Silva, M; Tarrio-Mosquera, J (KeAi Communications Co., 2021)
This research presents the results for analyses done to five geopotential global models (GGM), comparing them with ground data from GNSS and leveling in heterogenic zones from the geodetic perspective, in Chile and Spain. While the official and complete implementation of the International Height Reference Frame (IHRF) has not yet been established, the vertical geodetic system of many countries is not calculated on a global scale; instead, it is calculated by the variation of relative heights between one or more local tide gauges, such as in the case of Spain and Chile. This aspect creates regional and specific altimetry data, which disables the use of GGM to directly obtain the orthometric height of the vertical reference system (VRS) from the GNSS heights. Global models currently reach centimetric precision due to their high resolution but are directly incompatible for a local level. To solve this, we expose in this article the contrast between geometric geoidal undulation (ellipsoidal heights and orthometric data from the leveling networks in Spain and Chile) with the geoidal undulation in more recent models and higher resolution: Earth Gravitational Model 2008 (EGM08), European Improved Gravity model of the Earth by New techniques (EIGEN6C4), Gravity Observation Combination (GOCO05C), Experimental Gravity Field Model (XGM2016), and Ultra-High Resolution Global Geopotential Model (SGG-UGM), adjusting the residual between both referential heights by different parametric models and polynomials of determined order. Once evaluated, their geoidal undulations are combined with GNSS/leveling data from the corresponding VRS to generate a correcting surface, which is also known as a hybrid geoid, resulting in a model of optimal adjustment for the combination of five parameters of the EIGEN-6C4 with orthometric heights and ellipsoids of both Chile and Spain. The results show 2–3 cm precisions, which were statistically analyzed to determine the suitability for use. The final products are three grids of independent hybrid geoids, one for northern Spain and two for Chile (central and north), which allow continuous access to the VRS of each country using the GNSS s full potential until the IHRF is available and ready for use. © 2021 The Authors